The Role of Educational Environment of Pokhara University on Business Students’ Outcomes - Dhakal, Sunil; G.C., Surya Bahadur; Khatri, Bipin Thapa; Paudel, Samjhana (Journal of Business and Management, 2024)
Background: The students’ expectations, perceptions andevaluation impact the personal development. A sound education environment may help to improve higher education and build a good education system.Objectives: The purpose of this cross-sectional survey study is to empirically investigate how Pokhara University’s educational environment shapes business students’ development and their outcomes. The study focuses on the role of academic environment, curriculum, resource availability and student outcome. Through this study, we aim to identify the antecedents of business students’ outcomes.Methods: Using sample of 298 business students from different constituent and affiliated colleges of Pokhara university, from selected programs MBA, BBA and BBA-BI, the hypothesized relationships were tested through correlation, regression and mediation analysis.Results: Business students are positively impacted by the academic environment, availability of resources, curriculum, and quality of the educational system.Conclusion: Despite the recognized significance of the educational environment in higher education institutions like Pokhara University, there remains a scarcity of studies examining the dynamics between educational practices, innovation and student outcomes. This study fills a crucial gap by being among the first to empirically investigate how the educational environment, including curriculum alignment, academic settings, resources, and student support, influences business students’ outcomes. Additionally, it contributes to the existing literature by exploring the mediating roles of innovation and intellectual capital in this relationship.